Pengaruh Harga, Merek dan Kualitas Pelayanan Terhadap Keputusan Menjadi Customer Tetap Jasa Pengiriman - Fatimah Pohan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
The online buying and selling system has been very widely used by many groups which makes more and more parties need a third party as a safe delivery and intermediary for goods from the seller to the buyer, there is no buying and selling online, the distance from the closest person is also not an obstacle because it can only be sharing by sending goods through shipping services so that this shipping service business is very much in demand to open startup companies so that many competitors occur, one of which is competition to get customers or regular customers in various ways and mature strategies carried out to achieve company goals. In this study, we want to see the effect of price, brand and service quality which are closely related in getting regular customers, regular customers must be obtained even it is necessary to increase the number of regular customers, which means that the customer will always be loyal and loyal to one of the shipping services, this can increase value. companies and increasing the survival of the company in achieving its corporate goals, this study looks at whatever happens between each variable